Protective effect of quercetin on weight drop injury model-induced neuroinflammation alterations in brain of mice - Hmangte Hitler Kom, Mesram Nageshwar, Kota Srilatha, Karnati Pratap Reddy (Journal of Applied Pharmaceutical Science, 2019)
The neuroinflammatory response following traumatic brain injury is known to be a key secondary injury factor that can play a critical role in accelerating the progression of neurodegeneration. This study reports protective effect of dietary quercetin against neuroinflammation-induced changes in mice triggered by weight drop injury model. Quercetin is a natural flavonoid found in high quantities in fruits and vegetables, with properties of antioxidant, free radical scavenger, and anti-inflammation. Hence, this study reports the effects of quercetin on neuroinflammation-mediated oxidative stress and behavioral and histological alterations in mice. Mice were divided into four groups: control, inflammation, inflammation + Quercetin (20 mg/kg mass), and Quercetin (20 mg/kg mass). The treatments were carried out on mice for 7 days and subsequently, behavioral studies were conducted and then brains were collected and used for biochemical and histological studies. Mice undergoing inflammation showed significant (p < 0.05) deficits in motor coordination, increase in the paw withdrawal latency period, and levels of lipid peroxidation, as well as decline in the activities of antioxidant enzymes, such as superoxide dismutase, catalase, glutathione peroxidase, and histological alterations in cerebral cortex region in the brain compared with the control group. Quercetin treatment significantly (p < 0.05) reversed the behavioral alterations, decreased the lipid peroxidation level, and increased the superoxide dismutase, catalase, glutathione peroxidase activities, and histological alterations in cerebral cortex region of the brain compared with the inflammation group. These findings suggest that dietary quercetin has potential benefits in mitigating neuroinflammation-mediated oxidative stress and behavioral and histological alterations.
Keywords: Quercetin, weight drop injury, neuroinflammation, oxidative stress, histological alteration.